PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF PADA MATERI LETAK DAN LUAS BENUA ASIA DAN BENUA LAINNYA - Ambar Wisudanti (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2023)
The aim of research is to improve creative thinking skills student for subject “letak dan luas benua Asia dan Benua lainnya” by applying the Discovery Learning learning model.This research is Classroom Action Research which lasted for two cycles. The subjects of this research were students in class IX A of SMP Negeri 2 Girimarto in the 2022/2023 academic year, totaling 30 students. Data collection techniques were interviews, observations and tests, with data analysis in the form of content validity and triangulation. Classical completeness in cycle I was 66.67%, and research continued in cycle II with classical completeness 83.33%. Based on the research results, it can be concluded that creative thinking skills in social studies learning for class IX A students at SMP Negeri 2 Girimarto in the 2022/2023 academic year can be improved through the Discovery Learning learning model. The writer hope this research can make teachers more skilled in applying the Discovery Learning model to improve student’s creative thinking skills.